Endoscopic and Histologic Diagnosis of Upper Gastrointestinal Lesions, Experience in a Port City of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: For upper gastrointestinal tract disorders endoscopic biopsy is common procedure performed in the hospital for a variety of benign and malignant lesions. Endoscopy is incomplete without biopsy and histopathology is the gold standard for the diagnosis of endoscopically detected lesions.Methods: A prospective study was carried out at a private histopathology diagnostic center at Chittagong from October 2012 to September 2013. All the upper GIT endoscopic biopsy samples received during the period were included in the study. The endoscopy was done by a skilled endoscopist and his detail endoscopic findings were noted. After conventional tissue processing H&E stained slides are examined under light microscope by three competent histopathologists.Results: Among total 110 upper GIT endoscopic biopsy samples 22 (20%) were oesophageal, 73 (66.36%) gastric and 15 (13.64%) duodenal biopsies. Among oesophageal biopsies 18 (81.82%) were histologically neoplastic of which 13 (81.25%) were SCC and 03 (18.75%) adenocarcinoma. Rest 02 (9.09%) were leiomyoma. Among all the oesophageal carcinomas, 10 (62.5%) were provisionally diagnosed as carcinoma by endoscopists. Among 73 endoscopic biopsies from stomach, the mean age was 54.63 yrs. On histopathology among 73 patients, adenocarcinoma-33 (45.20%), gastric ulcer-11 (15.07%), gastritis-15 (20.55%) and hyperplastic polyp-14 (19.18%). Among 33 adenocarcinoma of stomach 23 (69.69%) were clinically diagnosed or suspected as carcinoma by the endoscopist. Among 15 duodenal biopsies 11 (73.33%) were diagnosed histologically as hyperplastic polyp, 02 (13.33%) as adenocarcinoma, 02 (13.33%) as ulcer. Among 110 UGIT biopsies total 51 (46.36%) were malignant. Mean age 59.49 yrs ranges from 22 Yrs to 82 Yrs. M:F ratio is 1.4:1. Among all 33 (64.7%) were gastric carcinoma, 16 (31.37%) oesophageal carcinoma and 02 (3.92%) duodenal carcinoma. Among 51, 35 (68.63%) were clinically diagnosed or suspected as carcinoma by endoscopist. No clinical information was available in 03 (5.88%) cases and rest 13 (25.49%) cases were clinically diagnosed as non neoplastic conditions by the endoscopist. Conclusion:Endoscopy followed by histopathological examination play important role for diagnosis and management of UGIT lesions.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.20997